(untitled) (SAARC Journal of Agriculture, 2023)
Root knot nematodes are sedentary parasites that form galls in plant roots thereby reducing the water and nutrient uptake to the plant, impeding the growth, hindering the fruit production, and cause yellowing of leaves and wilting. In this study, an attempt to understand the effect of increasing Meloidogyne incognita infestation on various biochemical parameters in spinach was made. Biochemical analysis of spinach plants with varied nematode inoculum was carried out in plastic pots. Four weeks after planting, freshly hatched second-stage juveniles (J2s) were used as inoculation at the rate of 500, 1000, 2500 and 5000 J2s per pot. Uninoculated plants served as control. Each experiment was replicated three times. After 45 days of inoculation, the plants were pulled out of the pots and analysed for changes in the following biochemical parameters: chlorophyll content, protein content, total phenolic content and defense enzymes (peroxidases and polyphenol oxidases). Plants inoculated with 5000 J2s showed significantly increased levels of peroxidase and polyphenol oxidase activity as compared to the control. Chlorophyll and protein content decreased while the total phenolic content was found to increase with increasing inoculum level. All these parameters showed little to no difference in plants inoculated with 500 J2s as compared to controls. SAARC J. Agric., 21(2): 53-66 (2023)